2022
DOI: 10.1038/s41598-021-04546-4
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoenvironmental proxies indicate long-term development of agro-pastoralist landscapes in Inner Asian mountains

Abstract: A growing body of archaeological research on agro-pastoralist populations of the Inner Asian mountains indicates that these groups adapted various systems of mobile herding and cultivation to ecotopes across the region from as early as 5000 BP. It has been argued that these adaptations allowed the development of flexible social-ecological systems well suited to the long-term management of these mountain landscapes. At present, less attention has been paid to examining the long-term ecological legacy of these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Multiple proxies for grazing also increase in the SG02 core from a forest opening at 2,800 m ASL after ca. 500 BP (Spate et al, 2022). These discontinuous phases of land use also parallel changes in the pollen record from Anchar Lake on the valley floor, where the intensification of agriculture after ca.…”
Section: Western Himalaya-hindu Kushmentioning
confidence: 63%
See 4 more Smart Citations
“…Multiple proxies for grazing also increase in the SG02 core from a forest opening at 2,800 m ASL after ca. 500 BP (Spate et al, 2022). These discontinuous phases of land use also parallel changes in the pollen record from Anchar Lake on the valley floor, where the intensification of agriculture after ca.…”
Section: Western Himalaya-hindu Kushmentioning
confidence: 63%
“…In these cases, new Bayesian age-depth models based on the Intcal20 curve were produced using the Bacon package in R (Blaauw and Christen, 2011;Reimer et al, 2020) prior to data examination (Supplementary Data). Ecological impacts of agropastoralism in the study regions observed by the authors during fieldwork also form an interpretive background to this study (Leipe et al, 2014a,b;Motuzaite Matuzeviciute et al, 2019;Spate et al, 2022). We also review several key palaeoclimate studies to contextualize human activity across the study region.…”
Section: Methodsmentioning
confidence: 77%
See 3 more Smart Citations